Metastasis of clear cell renal cell carcinoma to the larynx : a short literature review and presentation of a rare case of prolonged survival = Metastaza svjetlostaničnog karcinoma bubrežnih stanica u grkljan : kratki literaturni pregled i prezentacija rijetkog slučaja produljenog preživljavanja - Vrebac, Ilinko (Array, 2021)
Renal clear cell metastatic carcinoma of the larynx is an extremely rare diagnosis with poor survival. The objective of this short review is to provide insight into current state of literature on this rare neoplasm. Additionally we include the case of a patient with metastatic process of the thyroid cartilage that was treated with novel targeted therapies which enabled prolonged survival and good quality of life. These findings support their inclusion in treatment protocols of patients with metastatic renal clear cell carcinoma of the larynx, especially in those refusing surgery which is the main treatment option in literature so far.